2007
DOI: 10.1017/s0022278x07002558
|View full text |Cite
|
Sign up to set email alerts
|

Youth, globalisation, and millennial reflection in a Guinean forest town

Abstract: The last two decades have witnessed a surge in studies of youth culture and social practice. In Africa, as elsewhere, this body of youth-centred research and writing has devoted considerable attention to specific groups within a given country's young population, while largely neglecting others seen to lack either culturally innovative or politically subversive traits. Youths in large cities and young combatants involved in insurgency or counter-insurgency have shared centre stage in studies of youthful Africa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Restrictions on travel and internal movement by checkpoints occupation and in an environment of constant political violence. Some studies from South Africa, Northern Ireland and Palestine have shown that active participation and/or ideological commitment to political struggle can increase resilience and enhance coping strategies (Carins et al, 1989;Punamäki, 1996;Straker, 2007). Punamäki et al, in their series of studies in the Gaza Strip, found that stronger ideological commitment among Israeli children was related to fewer psychological problems and that higher exposure to traumatic events was likely to produce more commitment to their cause of liberation and protect children from the negative impacts of collective violence (Punamäki et al, 2004;Qouta et al, 2008).…”
Section: Witnessing Killings and Seeing Human Remainsmentioning
confidence: 99%
“…Restrictions on travel and internal movement by checkpoints occupation and in an environment of constant political violence. Some studies from South Africa, Northern Ireland and Palestine have shown that active participation and/or ideological commitment to political struggle can increase resilience and enhance coping strategies (Carins et al, 1989;Punamäki, 1996;Straker, 2007). Punamäki et al, in their series of studies in the Gaza Strip, found that stronger ideological commitment among Israeli children was related to fewer psychological problems and that higher exposure to traumatic events was likely to produce more commitment to their cause of liberation and protect children from the negative impacts of collective violence (Punamäki et al, 2004;Qouta et al, 2008).…”
Section: Witnessing Killings and Seeing Human Remainsmentioning
confidence: 99%
“…6 The trade unions' major demands were the creation of an inclusive government under a prime minster, the separation of powers, the fight against corruption and bad governance, and, most importantly, the general improvement of the population's living conditions (Camara 2014, 388-392). The government brutally reacted to the protests (International Crisis Group 2007a, 2007bHuman Rights Watch 2007a, 2007b. In February 2007, the trade unions and the government signed an accord.…”
Section: Women's Involvement In the General Strikes Of 2006 And 2007mentioning
confidence: 99%
“…Coast covers (parts of) the following countries: Gambia, (southern) Senegal, Guinea-Bissau, Guinea, Sierra Leone, and Liberia (Knörr and Filho 2010, 2). 3 See, for example, Claude Rivière (1971), Adamoleku Ladipo (1976), Lansiné Kaba (1976aKaba ( , 1976bKaba ( , 1977, Ibrahima Baba Kaké (1987), Alpha Ousmane Barry (2002), Mike McGovern (2002, Mohamed Saliou Camara (2005, Jay Straker (2007aStraker ( , 2007bStraker ( , 2009, Christian Højbjerg (2010), André Lewin (2010), Alexis Arieff and Mike McGovern (2013), Céline Pauthier (2013), Michelle Engeler (2019), and Anita Schroven (2019). 4 One of the MDG's eight primary goals was to promote gender equality and empower women, cf.…”
Section: Women and The Guinean State Since The Mid-1980smentioning
confidence: 99%
“…Research evidently featured an early preference for spectacular topics, often focusing on young males in some sort of conflict. While this has rightfully been criticized as potentially "enshrouding the continent in a mystique of otherness and exoticism" [117] (p. 315), the goal of such research was usually quite the opposite: to ground analyses of political violence in ethnographies of young people's quotidian experience. Contrary to the generalizing arguments about endemic corruption and African "neo-patrimonialism" as the hotbed of violent conflicts [100,[118][119][120][121], ethnographers of youth in violent settings attempted to show that these were in fact normal young people responding to exceptional circumstances [53,89,115].…”
Section: Ambivalent Youth: Makers and Breakersmentioning
confidence: 99%